Psychosocial Difficulties and Acquisition of Social Skills Among Preschool Children in Early Childhood Centres in Rivers East Senatorial District of Rivers State - Okankwu, Elizabeth Amini; Ekpo, Idongsit Ekaette (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2025)
The study investigated psychosocial difficulties and the acquisition of social skills among preschool children in early childhood centres in Rivers East Senatorial District of Rivers State. The study had two objectives, two research questions, and two corresponding null hypotheses. A correlational research design was adopted, targeting a population of 3,450 preschool children from 232 early childhood centres in Rivers East Senatorial District. A sample of 345 preschoolers was selected using a simple random method. Data were collected using two self-structured instruments: The Psychosocial Difficulties Checklist (PDC) and the Preschool Social Skills Checklist (PSSC). The instruments were validated by three experts in Primary Education Studies, and their reliability coefficients were established using the Cronbach Alpha method, yielding indices of 0.9 for PDC and 0.8 for PSSC. The collected data were analyzed using descriptive statistics (mean and standard deviation) to answer the research questions and inferential statistics (Regression and One-way ANOVA) to test the null hypotheses at a 0.05 significance level. Findings revealed a significant inverse relationship between hyperactivity and social skills acquisition, indicating that increased hyperactivity negatively impacts preschoolers' ability to develop essential social competencies. Additionally, social isolation was found to significantly affect the acquisition of social skills, as isolated children exhibited reduced engagement in peer interactions and social learning opportunities. Based on the findings, recommendations include incorporating psychosocial screening in school health services, implementing early intervention strategies, and encouraging parental and caregiver involvement to foster positive social development among preschoolers.